Structure and properties of spin-coated Ge25S75 chalcogenide thin films - Šlang, Stanislav; Janíček, Petr; Pálka, Karel; Vlček, Miroslav (My University, 2016)
Amorphous chalcogenide thin films of Ge25S75 composition have been deposited by spin-coating technique. Optical properties of thin films were investigated by spectroscopic ellipsometry in UV-MIR spectral range. Obtained results prove an increase of the thin films refractive index in the transparent region and a decrease of their thickness with increasing annealing temperature implying densification of the glass structure. Short wavelength absorption edge is shifting to lower energies (red shift) with increasing annealing temperature. Decreasing organic molecules content with increasing temperature of annealing was observed in MIR part of extinction coefficient and verified by Raman spectroscopy and EDS. Raman spectra also gave evidence of thermo-induced structural polymerization and decomposition of organic salts molecules yielding thin films with structure similar to the structure of the source bulk glass.
Struktura a vlastnosti spin-coatingem deponovaných tenkých chalkogenidových vrstev Ge25S75
Keywords: Glass and other amorphous materials; Thin films, optical properties; Thin films, other properties; Ellipsometry and polarimetry; Skelné a další amorfní materiály; Tenké vrstvy, optické vlastnosti; Tenké vrstvy, další vlastnosti; Elipsometrie a polarimetrie